Analysis of urea formaldehyde and urea-formaldehydeacrylamide resins using thermogravimetric method / Zaimatul Aqmar Abdullah and Nor Yuziah Mohd Yunus - Abdullah, Zaimatul Aqmar; Mohd Yunus, Nor Yuziah (Universiti Teknologi MARA Cawangan Pahang, 2019)
Formaldehyde emission reduction in panel products is critical and it can be partially controlled by using resin. As part of the emission reduction exercise, incorporation of acrylamide to urea formaldehyde (UF) was done for UF at molar ratio1.4. The produced UF and UF-acrylamide (UFA) were analyzed using Fourier Transform Infra-red (FTIR) for functional groups identification. Resins were also tested using thermogravimetric analysis (TGA) and the activation energy of both was determined using Kissinger method. The thermal decomposition profile for both samples followed similar trend. Two stages of decompositions were seen, where the first stage decomposed between 100 to 150°C, while the second stage ranges between 200 to 250°C. The low molecular weight material loss and degradation process was well defined. The activation energy was 130-140 kJ/mol for UFA and 150-170 kJ/mol for UF showing the UF resin to be more stable than UFA. Resultant panel product produced using UF and UFA, tested by Desiccator method, gave similar formaldehyde emission